2000
DOI: 10.1111/j.1529-8027.2000.22-46.x
|View full text |Cite
|
Sign up to set email alerts
|

Frequent Good Partial Remissions From Thalidomide Including Best Response Ever in Patients With Advanced Refractory and Relapsed Myeloma

Abstract: Twenty‐three patients with advanced and heavily pretreated myeloma were treated with thalidomide. Starting dose was 200 mg/d, and 20 patients had dose escalations up to 400 (n = 5), 600 (n = 12) or 800 mg/d (n = 3), usually in divided doses. Nineteen patients were refractory to recent chemotherapy, and four had untreated relapse after prior intensive therapy. Ten out of 23 patients (43%) achieved partial response (PR; nine with refractory and one with relapsed disease), six patients had minor response or stabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
58
1
2

Year Published

2002
2002
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(68 citation statements)
references
References 12 publications
7
58
1
2
Order By: Relevance
“…It must be pointed out that if our 11 patients with EMP are excluded, the response rate increases up to 58%. As previously reported, both the lack of response of soft-tissue plasmacytomas to thalidomide as well as the existence of cases of extramedullary progression despite serological response, even in patients with no extramedullary involvement at the start of thalidomide therapy, indicate that the homing of myeloma cells in the bone marrow is essential for the anti-myeloma effect of the drug and support the importance of the bone marrow microenvironment in the mechanism of anti-myeloma action of thalidomide (13,20,21,34).…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…It must be pointed out that if our 11 patients with EMP are excluded, the response rate increases up to 58%. As previously reported, both the lack of response of soft-tissue plasmacytomas to thalidomide as well as the existence of cases of extramedullary progression despite serological response, even in patients with no extramedullary involvement at the start of thalidomide therapy, indicate that the homing of myeloma cells in the bone marrow is essential for the anti-myeloma effect of the drug and support the importance of the bone marrow microenvironment in the mechanism of anti-myeloma action of thalidomide (13,20,21,34).…”
Section: Discussionsupporting
confidence: 69%
“…On the rationale of its antiangiogenic activity, thalidomide was the first of these new drugs. A response rate of about 40% has been consistently reported when using thalidomide as a single agent in myeloma patients with refractory or relapsed disease (11)(12)(13)(14)(15)(16)(17). When thalidomide is combined with other anti-myeloma agents the response rate increases to 50-63% (25)(26)(27)(28)(29)(30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous other investigators have reported similar results (Table 1) (Alexanian et al . 2000;Juliusson et al . 2000;Kneller et al .…”
Section: Thalidomide Monotherapy For Patients With Refractory or Relamentioning
confidence: 99%
“…1999). Since then, a number of reports have demonstrated the efficacy of thalidomide in 25-58% of refractory MM cases; treatment was associated with only minor complications such as somnolence, constipation, peripheral neuropathy, and skin rash (Alexanian & Weber 2000;Juliusson et al . 2000;Kneller et al .…”
Section: Introductionmentioning
confidence: 99%